2004
DOI: 10.1016/j.jacc.2003.07.032
|View full text |Cite
|
Sign up to set email alerts
|

Early interleukin-1 receptor antagonist elevation in patients with acute myocardial infarction

Abstract: Our study indicates that, unlike markers of necrosis, an increase of IL-1Ra levels occurs early in patients with AMI, is more significant in those with heralded infarction and symptom onset < or =3 h, and precedes the release of markers of necrosis. Thus, IL-1Ra determination may be an important early adjuvant toward the diagnosis of AMI in the ED.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
2

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(32 citation statements)
references
References 16 publications
(15 reference statements)
2
28
2
Order By: Relevance
“…IL-1Ra is an acute reactive protein and has been found to be prominently expressed at an early stage of acute myocardial infarction. 23) However, our data revealed that serum IL-1Ra levels were not correlated to either the CRP levels or the morphology of coronary plaque in patients with stable CAD.…”
Section: Discussioncontrasting
confidence: 62%
“…IL-1Ra is an acute reactive protein and has been found to be prominently expressed at an early stage of acute myocardial infarction. 23) However, our data revealed that serum IL-1Ra levels were not correlated to either the CRP levels or the morphology of coronary plaque in patients with stable CAD.…”
Section: Discussioncontrasting
confidence: 62%
“…7 Its levels are elevated early in patients presenting with ST-segment-elevation AMI, 5 and the greater the area of myocardium at risk is, the greater the increase in IL-1Ra levels is. 6 Moreover, in observational studies, higher IL-1Ra levels in patients with acute coronary syndromes were associated with unfavorable outcome.…”
Section: Il-1ra In Amimentioning
confidence: 99%
“…3,4 Like other acute-phase reactants, IL-1Ra levels increase during AMI, and its levels correlate with prognosis. 5,6 The role of increasing IL-1Ra during AMI is unclear, and speculations have been made that its role ranges from merely a marker of damage to a modulator of the inflammatory response to a potential cytoprotective agent. 5,8 Recently, forced expression of IL-1Ra in an animal model has been shown to be cardioprotective in terms of reduced infarct size and apoptosis.…”
mentioning
confidence: 99%
“…15 Indeed, because of its early release at sites of ruptured plaque, even before myocardial necrosis has occurred, IL-1ra was found to be elevated in patients presenting with ST-segment elevation myocardial infarction earlier than traditional markers of necrosis. 16 …”
Section: Cardiac-related Effects Of Il-1 and Il-1ramentioning
confidence: 99%